"Two Suns in One Firmament": John Cotton, Thomas Hooker, and the 1655 New Haven Sodomy Statute - Slater, Sandra (Church history, 2018)
This piece explores the origins of the anomalous 1655 New Haven statute against sodomy that broke with legal traditions and codes both in England and New England. A lengthy and extraordinarily specific piece of legislation, the New Haven law stands in stark contrast to the minimalist language favored by the English in the early seventeenth century. When viewed within the larger context of clerical animosities, particularly between Thomas Hooker and John Cotton, there is a strong circumstantial case to make for its implementation as an extension of John Cotton's rejected Massachusetts Bay legal code, Moses His Judicials, applied by his friend and admirer John Davenport in New Haven. A devout disciple of John Cotton, John Davenport's New Haven colony relied on Cotton's influence and stood as a rebuke to Thomas Hooker's Connecticut settlements, often criticized as too spiritually lax by those in Massachusetts Bay and New Haven. While seeking to demonstrate greater piety and rigidity, John Cotton and Thomas Hooker sought to exert dominance over the other, with Cotton employing Davenport's colony as an effective castigation of Hooker's perceived liberality. This piece is reflective of trends in studies of sexuality which suggest that ideas and identities related to sexuality do not operate in isolation, but often mirror anxieties not necessarily connected to the regulation of sexual activities. This article situates the 1655 Sodomy Statue within a broader context in order to understand its origins and animosities that potentially motivated its inclusion into the New Haven legal statutes.